2021
DOI: 10.1249/mss.0000000000002635
|View full text |Cite
|
Sign up to set email alerts
|

Nonplacebo Controls to Determine the Magnitude of Ergogenic Interventions: A Systematic Review and Meta-analysis

Abstract: Introduction: Placebos are used as a control treatment that is meant to be indistinguishable from the active intervention. However, where substantive placebo effects may occur, studies that do not include a non-placebo control arm may underestimate the overall effect of the intervention (active plus placebo components). This study aimed to determine the relative magnitude of the placebo effect associated with nutritional supplements (caffeine and extracellular buffers) by metaanalysing data from studies contai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 60 publications
2
19
0
1
Order By: Relevance
“…Indeed, there is considerable evidence to support placebo effects in sport and exercise nutrition, including sodium bicarbonate supplementation. In a recent meta-analysis, Marticorena et al [213] examined the effects of placebo ingestion compared to a nonplacebo control condition (no substance ingestion) on exercise performance in studies involving supplementation of caffeine and buffering agents (including sodium bicarbonate). In this meta-analysis, placebo ingestion was found to provide a small but ergogenic effect (Cohen's d = 0.09).…”
Section: Placebo Effects Associated With Sodium Bicarbonate Supplementationmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, there is considerable evidence to support placebo effects in sport and exercise nutrition, including sodium bicarbonate supplementation. In a recent meta-analysis, Marticorena et al [213] examined the effects of placebo ingestion compared to a nonplacebo control condition (no substance ingestion) on exercise performance in studies involving supplementation of caffeine and buffering agents (including sodium bicarbonate). In this meta-analysis, placebo ingestion was found to provide a small but ergogenic effect (Cohen's d = 0.09).…”
Section: Placebo Effects Associated With Sodium Bicarbonate Supplementationmentioning
confidence: 99%
“…In this meta-analysis, placebo ingestion was found to provide a small but ergogenic effect (Cohen's d = 0.09). Additional analyses from this review showed that around 30% of the performance-enhancing benefits of buffering agents could be attributed to the placebo effect [213]. A double-blind crossover design, in which all participants receive both the active treatment and placebo prior to performing an exercise task, is the study design most used when investigating the effect of sodium bicarbonate supplementation on exercise outcomes.…”
Section: Placebo Effects Associated With Sodium Bicarbonate Supplementationmentioning
confidence: 99%
“…A recent meta-analysis explored the effects of placebo ingestion compared with a no-placebo control condition (i.e., no substance ingestion) [94]. This analysis reported that placebo ingestion provided a small but significant ergogenic effect (Cohen's d: 0.09) [94].…”
Section: Placebo Effects Of Caffeine On Resistance Exercisementioning
confidence: 99%
“…Collectively, these findings support consideration of more holistic approaches to intervention delivery. Factors that may influence an individual's response to intervention include nutritional status (both acute and chronic), physical activity levels, sleep, environmental conditions, and external sources of motivation (Mann et al, 2014) such as intervention expectancy (Marticorena et al, 2021). A logical next step for future research would be to attempt to parse out the relative influence of these factors on individual response variation, although this is undoubtedly challenging.…”
Section: Discussionmentioning
confidence: 99%